Comprehensive Physiology 2016
DOI: 10.1002/cphy.c140064
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Flexibility: Hibernation, Torpor, and Estivation

Abstract: Many environmental conditions can constrain the ability of animals to obtain sufficient food energy, or transform that food energy into useful chemical forms. To survive extended periods under such conditions animals must suppress metabolic rate to conserve energy, water, or oxygen. Amongst small endotherms, this metabolic suppression is accompanied by and, in some cases, facilitated by a decrease in core body temperature-hibernation or daily torpor-though significant metabolic suppression can be achieved even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 307 publications
(351 reference statements)
2
122
0
1
Order By: Relevance
“…The ability of animals to face prolonged periods of food shortage is under strong natural selection (Geiser and Stawski, 2011;Lindstedt and Boyce, 1985;McCue, 2012;Millar and Hickling, 1990;Staples, 2016). Body reserves (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of animals to face prolonged periods of food shortage is under strong natural selection (Geiser and Stawski, 2011;Lindstedt and Boyce, 1985;McCue, 2012;Millar and Hickling, 1990;Staples, 2016). Body reserves (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Some mammalian species have the ability to suppress the metabolic rate to conserve energy, water, or oxygen to survive extended periods of food restriction. This metabolic suppression is often accompanied by a decrease in core body temperature, that is, hibernation or daily torpor (Staples, 2016). Fujita et al (2013) identified a bovine hibernation-specific protein complex in Holstein non-pregnant cows that increased as soon as fasting commenced.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial substrate oxidation capacity is markedly decreased, especially for succinate but also with NADH-linked substrates, during the torpor phase of hibernation (Staples, 2014(Staples, , 2016. As discussed above, a decrease in mitochondrial capacity for substrate oxidation may affect the production of H 2 O 2 more than the pathways for its consumption, thereby decreasing [H 2 O 2 ] ss .…”
Section: Mammalian Torpor and Hibernationmentioning
confidence: 98%
“…As discussed above, a decrease in mitochondrial capacity for substrate oxidation may affect the production of H 2 O 2 more than the pathways for its consumption, thereby decreasing [H 2 O 2 ] ss . However, there are indications that proteomic and allosteric regulation of mitochondrial substrate oxidation may form part of the adaptation to torpor (reviewed in Staples, 2014Staples, , 2016. Posttranslational modifications such as glutathionylation may decrease enzymatic flux and, at the same time, either decrease or increase ROS production as seen with complex I and II, respectively (reviewed in Mailloux and Treberg, 2016).…”
Section: Mammalian Torpor and Hibernationmentioning
confidence: 99%